The impact of location, price, and diversity of products on buying interest in Omega Tirosa Store - Thomas Austheen Lasa; Ni Wayan Wijayanti (Universitas Pendidikan Nasional, 2021)
This study aims to determine the relationship between variables, location, price, and product diversity on buying interest in Omega Tirosa Store in Denpasar City conducted in September 2019 to December 2019 by using respondents in Denpasar City. The number of samples taken was 150 respondents using the method of nonprobability sampling, i.e., purposive sampling. Location, Price, and Product Variability Variables were collected using a questionnaire. The results of the multiple linear regression analysis show that the Location, Price, and Product Variability variables have a positive and significant relationship to Purchase Interest shown by each value (Location, 0.103) (Price, 0.205) Product Diversity (0.236). Determination Coefficient Test results show that the Location, Price, and Product Variability Variables influence 17.1% of Purchase Interest, while 82.9% of other variables are not needed. The conclusions that can be drawn from this study are positive and significant locations on the buying interest of Denpasar Omega Tirosa Store, Positive and significant prices on the buying interest of Denpasar Omega Tirosa products, and Product diversity that is positive and significant on the buying interest of Denpasar Omega Tirosa Store, Location, Prices, and Product Diversity together positively and significantly towards buying interest in Omega Tirosa Store in Denpasar. This refers to research showing increasing consumer buying interest Omega Tirosa Store must pay attention to the selection of business locations, directing the prices given to consumers as well as the diversity of products supported.